Rebellion and modernity in Marcel Duchamp: a new definition of subject and artistic object (Palíndromo, 2014)
The essay attempts to discuss the works of Marcel Duchamp in the first half of twenty century, examining his rebels proposal in the political-institutional en- vironment of his time and a specific ques- tion: the relation between Art and Concept in this production, attempting to the ways in which ones de redefinition of the artis- tic space and the artistic object conduces to propose a new notion of Art and a new notion of Artist. Such redefinition shows a significant politic value, since it situates the artist as a rebel able to question the exis- ting order and an institutional discourse that seeks to frame the art object within predictable limits.
Keywords: modern art; Marcel Duchamp; art and concept